Perancangan Sistem Inventaris Barang di Bank Sumsel Babel Cabang Pembantu Lemabang - Muhammad Wahyu Oktiyawan; Muhammad Kadafi (Unversitas Muhammadiyah Riau, 2022)
The performance of an assignment to each job requires much of the role of technology to support the activities to be carried out. The role of technology makes every activity more effective and efficient and treated information more precise and accurate. Bank Sumsel Babel Capem Lemabang is an organization that is financially oriented and this the one of organization that has developed considerable information. But at the asset inventory processing in Bank Sumsel Babel Capem Lemabang still USES Microsoft excel which has no database system. This would require an inventory system to record assets Bank Sumsel Babel Capem lemabang had to tidy up and make the annual report easier. It is hoped that with this inventory system Bank Sumsel Babel Capem Lemabang asset recorders could help asset recorders be more organized and structured. The design of the system will use DFD and erd, and for the database will use mysql, the system will be developed using the waterfall method.